The enviro-champs: establishing a framework for a technologically upgraded environmental monitoring network at community scale - Pattinson, N. B.; Taylor, J.; Lepheana, A. T.; Dickens, Chris W. S.; Graham, P. M. (International Water Management Institute, 2023)
The Enviro-Champs initiative was developed as a community driven, citizen science initiative in Mpophomeni township in Kwa-Zulu Natal (KZN), South Africa. Over time, the scope of work done and data collected by the Enviro-Champs has expanded. There is now recognition both locally and globally that the Enviro-Champs initiative shows great promise for national and global upscaling. However, several areas within the initiative remain where it could be improved, especially technologically. GroundTruth, in conjunction with technical and funding support from CGIAR Research Initiative on Digital Innovation and the International Water Management Institute (IWMI), engaged in a project which aimed to i) establish recruitment, training, and education tools to support establishment of a technologically integrated and upgraded Enviro-Champs initiative, ii) develop an outline for a training and education workshop for Enviro-Champs once they are hired, iii) improve data collection and reporting capacity and efficiency with a sustainable system (in collaboration with CGIAR and FormShare), and iv) pilot test technological improvements to the Enviro-Champs initiative within the Mpophomeni Enviro-Champs in conjunction with the South African National Biodiversity Institute (SANBI), and Umgeni Water. The overarching aim was to develop a technologically innovative and upgraded best-practice framework for the Enviro-Champs, from recruitment, through training and data collection, to data management and reporting. The primary outcome was to have a fully functional, digitally improved Enviro-Champs system in Mpophomeni, that could serve as a working template for upscaling the Enviro-Champs initiative elsewhere in Southern Africa or the world. This report reflects the process and outcomes of this project to date.